2019
DOI: 10.1002/jts.22392
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Disaster Exposure and Mental and Physical Health Symptoms Among a Large Sample of Gulf Coast Residents

Abstract: A large body of research has linked disaster exposure to adverse mental and physical health outcomes. Few studies, however, have explored the cumulative impact of exposure to multiple disasters. Participants (N = 8,366) from the National Institute of Environmental Health Sciences Gulf Long-Term Follow-Up Study were classified as having been exposed to both, either, or neither Hurricane Katrina and the Deepwater Horizon oil spill (DHOS). Participants also reported on a range of mental and physical health sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 39 publications
3
48
2
1
Order By: Relevance
“…43,44 Such events expose inequities in areas including access to quality housing and education as well as issues of economic and environmental justice that create conditions that make it difficult to maintain health. 45 After all types of disasters, minority communities have been documented in the literature to be faced with a disproportionate share of detrimental physical and mental health outcomes. 45−47 These disparate health impacts may be due to an inability to fully understand warning advisories related to an impending hazard event or further caused by living in areas of high hazard vulnerability and poor access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Such events expose inequities in areas including access to quality housing and education as well as issues of economic and environmental justice that create conditions that make it difficult to maintain health. 45 After all types of disasters, minority communities have been documented in the literature to be faced with a disproportionate share of detrimental physical and mental health outcomes. 45−47 These disparate health impacts may be due to an inability to fully understand warning advisories related to an impending hazard event or further caused by living in areas of high hazard vulnerability and poor access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…They support the importance of using a developmental approach to understand the longer‐term effects on children of exposure to multiple disasters and other traumatic events which can contribute to both risk and resilience. Complementing these findings, data from other studies on disasters, including exposure to multiple disasters, showed increased risk for mental health problems for children and families (Lowe et al, 2019; Osofsky et al, 2015).…”
Section: The Impact Of Hurricane Katrina On Children and Familiesmentioning
confidence: 59%
“…Studies of residents of the Gulf Coast region experiencing both Hurricane Katrina and the Gulf Oil Spill provided the opportunity to gain more understanding about the effects of cumulative disaster exposure and the impact on behavioural health. Lowe et al (2019) studied mental and physical health symptom data from 8366 participants who were part of the National Institute of Environmental Health Sciences Gulf Long‐Term Follow‐Up Study and reported on the impact of being exposed to Hurricane Katrina and the Gulf Oil Spill. They found that exposure to multiple disasters contributed to increased risk for adverse mental and physical health symptoms.…”
Section: The Impact Of Hurricane Katrina On Children and Familiesmentioning
confidence: 99%
“…While individuals with mental health concerns may be less likely to seek or receive care during acute disasters, there is likely to be a surge in service need that may last years after the events (Lowe et al, 2019). It is therefore important for health service researchers to examine short and long term population-level responses (e.g.…”
Section: Treatment and Health Services Researchmentioning
confidence: 99%